New Nitro Diazo Dye Vanillin Derivatives, Synthesis and Characterization - Abdalrahem Bin Selim, Elham; Hadi Al–Douh, Mohammed; Mahfoudh Yusr, Khulood (Al-Nahrain Journal of Science, 2024)
The diverse applications of azo compounds as reagents to bring about chemical synthesis is one of the fastest-growing areas of research. It is well known that the position of the substituents has an important role in the effect of the medicinal, dye industry, thermal, and optical properties of the compounds. In this work, we limit our studies to synthesizing two new diazo dye vanillin derivatives starting from aniline. Nitro aniline compounds 10 and 12 were prepared starting from aniline, and new nitro diazo vanillin derivatives were obtained 4 and 5. Through coupling reactions with vanillin 15 via diazonium salts, 4-hydroxy-3-methoxy-5-((2,4-dinitrophenyl)diazenyl)benzaldehyde 4 was obtained from 2,4-dinitroaniline 10, while 4-hydroxy-3-methoxy-5-((2,4-6,trinitrophenyl)diazenyl)benzaldehyde 5 resulted from 2,4,6-trinitroaniline 12. The synthesized compounds were characterized by spectroscopic methods; UV-Vis., FTIR, MS, and 1HNMR and melting point determination. The results of the reactions gave good yields of all products.